2016
DOI: 10.1097/ncc.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oncology Patients’ and Their Family Caregivers’ Attitudes and Concerns Toward Pain and Pain Management

Abstract: Patients and FCs need education about perceived barriers to effective pain management. They should be coached together to maintain or increase the congruence between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Although there are no randomized trials comparing marijuana and prescription opioids for cancer‐related pain, patients are increasingly reporting the use of cannabis as a substitute for prescription opioids . Oncology patients may have apprehensions about opioids, including a fear of dependence and potential side effects . Indeed, the most commonly reported motivation for opioid misuse is relief from physical pain, yet these fears introduce potential barriers to effective cancer pain management .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are no randomized trials comparing marijuana and prescription opioids for cancer‐related pain, patients are increasingly reporting the use of cannabis as a substitute for prescription opioids . Oncology patients may have apprehensions about opioids, including a fear of dependence and potential side effects . Indeed, the most commonly reported motivation for opioid misuse is relief from physical pain, yet these fears introduce potential barriers to effective cancer pain management .…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Oncology patients may have apprehensions about opioids, including a fear of dependence and potential side effects. 42 Indeed, the most commonly reported motivation for opioid misuse is relief from physical pain, 31 yet these fears introduce potential barriers to effective cancer pain management. 42 Medical marijuana legalization has been associated with a 23% reduction in hospitalizations related to opioid dependence or abuse, and this suggests that if patients are in fact substituting marijuana for opioids, this substitution may reduce the risks of opioid-related health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large study of 4707 cancer survivors revealed that two‐thirds reported at least 1 barrier to cancer pain management, with the most vulnerable groups—those who were nonwhite, less educated, older, or having more comorbidities—being most adversely affected . Numerous studies have examined specific barriers expressed by patients and family/caregivers regarding pain and pain management, with fears of addiction consistently being cited as a substantial concern . Physician barriers to cancer pain management include inadequate assessments and a reluctance to administer and prescribe opioids .…”
Section: Introductionmentioning
confidence: 99%
“…However, three cases of eye distention were found with duloxetine treatment in our study. The observed mean difference in FACT-Tax pain score between the duloxetine and any other anti-neurotoxicity groups in paclitaxel chemotherapy regimens was larger than that reported by Goldstein (23). Duloxetine-related clinically meaningful improvement in other PIPN symptoms, such as weakness, joint pain, or muscle cramps, may be directly comparable with painful chemotherapyinduced peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 54%